2012
DOI: 10.1016/j.ophtha.2012.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Grading Reproducibility during the Comparison of Age-related Macular Degeneration Treatments Trials

Abstract: OBJECTIVE To report Reading Center reproducibility during grading of Optical Coherence Tomography (OCT, Carl Zeiss Meditec, Dublin, California) images obtained during the Comparison of Age-Related Macular Degeneration Treatments Trials (CATT). DESIGN Prospective clinical trial PARTICIPANTS Independent reading teams reevaluated 270 OCT scans randomly sampled from the first 2 years of CATT enrollment. To assess temporal drift, a cohort of 23 scans submitted during the initial portion of the CATT study was lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 33 publications
0
52
0
1
Order By: Relevance
“…8,10,19 From long reading center experience, manual segmentation is less prone to serious segmentation errors when readers are well trained, as shown by intra- and inter-reading center reproducibility studies, 20,21 but no individual reader can locate a clearly outlined border as accurately as a standardized algorithm, especially if complete data sets of 3-dimensional information are included. Moreover, data from large samples and huge populations are not accessible for manpower-based analysis.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,19 From long reading center experience, manual segmentation is less prone to serious segmentation errors when readers are well trained, as shown by intra- and inter-reading center reproducibility studies, 20,21 but no individual reader can locate a clearly outlined border as accurately as a standardized algorithm, especially if complete data sets of 3-dimensional information are included. Moreover, data from large samples and huge populations are not accessible for manpower-based analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed discussion of the methodology for the CATT has been published previously 12-14 . From February 2008 through December 2009, 1185 patients from 43 clinical centers in the United States were enrolled into the trial.…”
Section: Methodsmentioning
confidence: 99%
“…The CATT study procedures have been previously published and can be found on ClinicalTrial.gov (study identifier, NCT00593450). 7, 8 Briefly, 1185 patients with neovascular AMD were enrolled in CATT at 43 clinical centers in the United States. Patients were randomly assigned to one of four treatment groups: 1) ranibizumab monthly, 2) bevacizumab monthly, 3) ranibizumab pro re nata (PRN), or 4) bevacizumab PRN.…”
Section: Methodsmentioning
confidence: 99%